(untitled) (Tri-Chandra Journal of Anthropology, 2025)
Climbing Sherpas have been a crucial part of the adventurous yet perilous high- altitude mountaineering pursuits in the Himalaya. Growing commercialization after the groundbreaking 1953 Everest ascent has led to unprecedented changes in the ethnic Sherpa identity as well as the mountaineering industry in Nepal, of which Mount Everest is an integral part. Drawing on an ethnographic study in 2019, 2020 and 2024 in Nepal, the present article explores the contours of the climbing vocation in contemporary Nepal. The findings reveal that ethnic Sherpas have claimed more pronounced roles as international mountain guides, base camp managers and tourism outfitters. Additionally, there has been a notable increase in participation from non- Khumbu Sherpas and non-Sherpas in Nepali mountaineering thus paving the way for diversity within the industry. This article explores the dangers of working on the mountains, and delves into the unparalleled changes that have taken place in the last seventy years within Nepalese mountain climbing and in the lives of the climbing sherpas, including what the profession entails.